Peningkatan Hasil Belajar IPS Peserta Didik Sekolah Dasar melalui Model Pembelajaran Problem-Based Learning: Improving Elementary Students’ Social Studies Learning Outcomes through the Problem-Based Learning Model - Islahuddin (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2025)
This research aims to improve student learning outcomes by applying a problem-based learning model in social studies subjects in grade V of SD Inpres 3 Tondo. This study uses experimental methods with pre-test and post-test designs. The results of the study show that the problem-based learning model can improve the learning outcomes of students in grade V Of Elementary School Inpres 3 Tondo. This study also found that problem-based learning models can improve students' ability to understand subject matter and increase learning motivation. In addition, this study also found an improvement in students' skills in critical thinking and effective communication. Therefore, the problem-based learning model can be used as an alternative to improve student learning outcomes, improve the quality of learning, and improve students' skills in critical thinking and effective communication.